A COMPREHENSIVE EVALUATION OF DIGITAL TRANSFORMATION ACROSS MULTIPLE BUSINESS FUNCTIONS IN SOUTH AFRICAN SMMES: INSIGHTS POST-COVID-19 - Nomfundo Gladys Khoza; Walter Mthuthuzeli Mkosana (Journal of Management Small and Medium Enterprises (SME's))
The digital transformation of Small, Medium, and Micro Enterprises (SMMEs) is crucial for maintaining competitiveness and ensuring long-term growth in today’s business environment. This systematic literature review evaluates how digital technologies have reshaped business functions within South African SMMEs, particularly following the COVID-19 pandemic. Articles published between 2019 and 2024 were sourced from Scopus and Web of Science, and the PRISMA framework was used for selecting and analysing relevant studies. The review assesses the current state of digital transformation, exploring its impact on marketing, operations, customer engagement, and decision-making processes. It identifies key challenges, such as resource limitations, digital skills gaps, and infrastructure constraints, which impede widespread digital adoption. Sector-specific insights are also provided, recognizing varying levels of digital maturity across industries. The findings offer actionable recommendations for SMME owners, policymakers, and educators, suggesting strategies to accelerate digital adoption. By providing valuable local data, this study adds to the growing body of research on entrepreneurship and digitalization in South Africa’s post-pandemic landscape. The study underscores the need for targeted interventions to help SMMEs overcome barriers and fully leverage technology to drive growth and innovation.